2020
DOI: 10.1109/tcomm.2020.2978182
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Construction of Multiple Complete Complementary Codes and Asymptotically Optimal Aperiodic Quasi-Complementary Sequence Sets

Abstract: In recent years, complementary sequence sets have found many important applications in multi-carrier code-division multiple-access (MC-CDMA) systems for their good correlation properties. In this paper, we propose a construction, which can generate multiple sets of complete complementary codes (CCCs) over ZN , where N (N ≥ 3) is a positive integer of the form N = p e 0 0 p e 1 1 . . . p e n−1 n−1 , p0 < p1 < · · · < pn−1 are prime factors of N and e0, e1, · · · , en−1 are non-negative integers. Interestingly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…Analysing closely the results of [32], [33] and [34] it is being observed that the number of CCC's and eventually the set size of the QCSS are small when N is 3 or have the smallest prime factor 3. Also it has been observed in all the previous constructions [32]- [34] that the optimal QCSS are designed over Z N , where N always a prime, power of prime or an odd integer, depending on the constructions. To overcome these problems, in search of new approaches to design QCSSs over any alphabet size N, we propose several sets of CCCs and eventually QCSSs using Florentine rectangles.…”
Section: Referencesmentioning
confidence: 68%
See 4 more Smart Citations
“…Analysing closely the results of [32], [33] and [34] it is being observed that the number of CCC's and eventually the set size of the QCSS are small when N is 3 or have the smallest prime factor 3. Also it has been observed in all the previous constructions [32]- [34] that the optimal QCSS are designed over Z N , where N always a prime, power of prime or an odd integer, depending on the constructions. To overcome these problems, in search of new approaches to design QCSSs over any alphabet size N, we propose several sets of CCCs and eventually QCSSs using Florentine rectangles.…”
Section: Referencesmentioning
confidence: 68%
“…The main difference of this construction with all the previous constructions is that here we can construct asymptotically optimal and near-optimal QCSS over Z N for any N > 3, whereas previously N ≥ 5 was only odd integer [34], prime [32], [33] or power of prime [32]. For comparing the parameters with the exixting results, in Table VI, K prev and ρ prev denote the previous set size and the previously reported optimality factor, respectively, of the QCSS over Z N , for some values of N, when N has a prime factor 3.…”
Section: Comparison With Previous Workmentioning
confidence: 92%
See 3 more Smart Citations